Work and organizations in China after thirty years of transition (Bingley, UK : Emerald, 2009)
Thirty years of economic change have fundamentally altered the nature of organizations and work in China. This volume brings together current research by many of the top scholars studying these issues and provides a glimpse into the state of thinking on organizations and work at the start of the fourth decade of transition. The topics covered include the continued transition of State Owned Enterprises, the emergence of asset management companies, the adoption of innovative labor structures, connections between organizational processes and worker outcomes, the changing use of networks in job search, and role of work and work units in creating and maintaining inequality.
Includes bibliographical references.
Description based on print version record.
Keywords: Industrial organization -- China; Business enterprises -- China; Labor -- China; Sociology: work & labour; Social Science -- Sociology -- General